Consumer Protection Against Misleading Advertising: Individual Voluntary Arrangements - Duffey, Rachel (2008)
In recent months there has been widespread debate regarding the advertising of Individual Voluntary Arrangements (IVAs). Several large providers have been found guilty of misleading consumers through their advertisements and many within the credit industry have accused so called ÃÂ¢ÃÂÃÂIVA factoriesÃÂ¢ÃÂÃÂ of targeting vulnerable consumers and persuading them to enter into an arrangement when an alternative would be more appropriate.